Rekayasa proses produksi resin alkid dari minyak nyamplung - Ika Amalia Kartika; Natasha Yuka Fastiana; Danu Ariono (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Calophyllum is a potential plant in Indonesia where the area is very wide spread besides almost all parts of Calophyllum plants can be utilized. The study aims to produce alkyd resin from Calophyllum oil so the usefulness of Calophyllum plants can be optimized. The synthesis of alkyd resin was carried out by variations in oil to glycerol mole ratio (1:3, 1:4, and 1:5) and temperature (230 and 250C). Acid and iodine values, density, viscosity, drying time, color, solubility, thermal stability, and functional groups analyzed the alkyd resin quality. The oil-to-glycerol mole ratio and temperature variations affected the acid value, viscosity, color, and drying time. Higher temperatures and more glycerol affected the reaction time, and the drying time of alkyd resin became faster. In addition, its viscosity decreased, and its thermal stability was stable. With the high addition of glycerol at low temperatures, the color of alkyd resin was bright, but it became darkened at higher temperatures. Calophyllum-based resins owned the fastest alkyd resin drying time without passing through the drying and purifying process, which was 60 minutes at 50°C